THE INFLUENCE OF E-LEARNING CHARACTERISTICS AND BASIC ICT COMPETENCIES TO ACTUAL USAGE OF E-LEARNING: A PATH DIAGRAM MODEL - I Made Suarta; I Ketut Suwintana (Jurnal Sistem Informasi, 2015)
In this paper, the Technology Acceptance Model (TAM) is extent with two external stimulus namely e-learning characteristics and basic ICT (Information and Communication Technology) competencies. The purpose of this study are (1) finding relationship between e-learning characteristics and lecturers’ basic ICT competencies with the perceived ease of use and perceived usefulness of e-learning; and (2) determining the effect of e-learning characteristics and lecturer basic ICT competencies to the actual usage of e-learning. Research subjects are Bali State Polytechnic lecturers who have attended the elearning training. In this study, to collect the data sample, a non-random sampling technique is adopted. The data is collected by self-administered questionnaires and is analyzed using structural equation modeling. Basic ICT competencies of the Bali State Polytechnic lecturers are good, but the level of actual usage of e-learning is very low. Basic ICT competence shows no significant effect on the perceived ease of use and perceived usefulness of e-learning. The actual usage of e-learning also has low implications. E-learning characteristics show a significant effect on perceived ease of use and perceived usefulness of e-learning, which implies the change attitude and behavior in the use of elearning. Characteristics of e-learning become a determinant factor in the adoption and use of elearning. The findings will help lecturer a better understanding to the mechanism of e-learning adoption. The study recommends for polytechnic institutions to make a systematic effort to provide lecturers with training on how to use e-learning system effectively. A further research to identify other factors that may influence lecturers' attitudes toward the adoption of e-learning system is demanded following this research.